Reducing Maori and Pacific Inequalities - Ron Crawford (New Zealand Government, The Treasury, 2001)
Over the last fifty years the Maori and non-Maori populations have slowly and unevenly become more similar on a range of key demographic, social and economic outcomes. This has principally been driven by increased geographic and social proximity between the two groups. There is evidence that similar processes may be operating for migrant peoples from the Pacific. Many Maori and Pacific people do better than the population median. Conversely, on most outcomes, a much greater number of people other than Maori and Pacific people do worse than the median. Nevertheless, it remains true that Maori and Pacific people are disproportionately represented in the group that do worse than the median. In this paper, we consider priorities for action aimed at improving outcomes for those Maori and Pacific people, who do worse than the median population. The companion working papers prepared for Treasury's "Inclusive Economy" key priority explore other aspects of social and economic inclusion within New Zealand. The paper sets out a preliminary framework to assist Ministers to identify policy and spending priorities for strengthening policy for reducing these disparities. It identifies policy areas and general design issues pivotal to accelerating a reduction in disparities. The paper draws on New Zealand and international evidence to understand the mechanisms that perpetuate disparities, and to identify policies that can better address them. The paper concludes that policy should address its primary effort to improve outcomes for those Maori and Pacific people who do worse than the median for the population, while, at the same time assisting others who have similarly poor outcomes. It suggests that improving literacy and numeracy skills of Maori and Pacific students at primary school level is a priority for further development. It also recommends programmes in the health, employment and housing sectors to back this up.
Keywords: H0; I0; I3; 330; disparity; inequality; Maori; Pacific people